Musical Excellence: Strategies and Techniques to Enhance Performance - Williamon, Aaron (Oxford Oxford University Press, 2004)
Williamon has garnered the collective expertise of an impressive array of music scholars to produce a book of quality. Different chapters in the book will be variously useful for academics, teachers and both music research and performance students. It will be a worthwhile addition to all Conservatoria libraries.Musical Excellence is an inspirational collection of articles on achieving excellence in musical performance, based on empirical, cross-disciplinary research within the context of theories of human performance and cognition...it should be very much welcomed by the music profession, including performers, teachers, students and researchers, as it offers a valuable foundations to inform empirically the training of practitioners for the acievement of artistic potential (British Journal of Music Education Vol 23, No 1 )The Williamon book, while providing excellent summaries of current research, is intended to influence the way in which musicians are trained and perform, and consequently should be read by music teachers and performers, as well as by those of us with an interest in music science. The relationship between researchers and professional performing musicians has been tenuous. The Williamon book seeks to bridge this divide by providing clear recommendations for practices that will improve musical performance along with a synopsis of the scientific basis for these recommendations. (Psychology of Music Vol 33, No 4 )This is a book of high quality that provides a wealth of useful information for both practicing musicians and researches in music psychology and medicine. (Psychology of Music, Vol 9 )A fascinating new book published by OUP. This is a collection of essays, edited by Aaron Williamon, about strategies and techniques designed to enhance performance. Some of the contributions are tough going but are rewarding. Performers at all levels will be interested (and probably helped) by the revelation of scientifically grounded ways of enabling them to achieve their potential artistically. Those who achieve greater control over their mental and physical state can often surpass their own expections. Musicians will be specially interested by the chapters on ways of avoiding the chronic pain and discomfort that seem to be inseparable from playing most instruments. Poor posture, bad practice technique and stress account for most of these ills... Music teachers should study this unusual - probably unique - book. Musical performance is a strenuous and demanding life, but ways of lessening the physical strain can only be welcomed and absorbed. (Sunday Telegraph )A certain mystique has perhaps surrounded high-level musical achievement and this book dispels ambiguity, offering ideas that can direct all musicians to their best efforts. Individual practice strategies, memorizing, sight reading, improvisation and effective rehearsing are all addressed. Physical and mental fitness, pre-performance routines through selected relaxation and visualization techniques, the impact of drugs, expressivity, are appraised in the context of occupational stress... These studies clearly show that applied research can and does facilitate the musician's quest for excellence and will continue to do so. Gone is the concept of the lofty musician in his gilded cage, guided by mysterious powers. In our quest towards lofty ideals we need first to understand the physicality and the psychology of what constitutes a musician. This pragmatic book guides us towards that goal. (To appear in future issue of Stringendo or the Australian Music Teacher )
Keywords: Performance